2005
DOI: 10.1093/carcin/bgi249
|View full text |Cite
|
Sign up to set email alerts
|

Sequence specificity of Cr(III)–DNA adduct formation in the p53 gene: NGG sequences are preferential adduct-forming sites

Abstract: Hexavalent chromium [Cr(VI)] is a known etiological factor in human lung cancer. Cr(VI) exposure-related lung cancer has a high mutation incidence in the p53 gene. Upon intake in human cells Cr(VI) is reduced to Cr(III), which is able to conjugate with amino acids and consequently form either binary Cr(III)-DNA or ternary Cr(III)-amino acid-DNA adducts. Both binary and ternary Cr(III)-DNA adducts are mutagenic. We have found that the Escherichia coli nucleotide excision enzyme UvrABC nuclease is able to incise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
2
34
1
Order By: Relevance
“…Hexavalent chromium (Cr(VI)) is another environmental genotoxic agent that induces a spectrum of adducts including bulky lesions that are repaired by NER (25). Evidence indicates that Cr(VI) preferentially reacts with guanine runs (26), which predicts that telomeres are also susceptible to Cr(VI)-induced lesions. Consistent with this, we previously reported that Cr(VI)-induced replication stress causes telomere loss and aberrations (27).…”
Section: Introductionmentioning
confidence: 99%
“…Hexavalent chromium (Cr(VI)) is another environmental genotoxic agent that induces a spectrum of adducts including bulky lesions that are repaired by NER (25). Evidence indicates that Cr(VI) preferentially reacts with guanine runs (26), which predicts that telomeres are also susceptible to Cr(VI)-induced lesions. Consistent with this, we previously reported that Cr(VI)-induced replication stress causes telomere loss and aberrations (27).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have found that UvrABC incision shows great sequence specificity for Cr(III)-modified DNA and Cr(III)-His-modified DNA and that the sequence specificities for both types of modified DNA are identical (8). Together, these results lead us to hypothesize that the NER system recognizes the guanine adduct, whether it is a Cr(III)-ligand-DNA or a Cr(III)-phosphate-DNA adduct, but not Cr (III)-phosphate complexes (8).…”
Section: Discussionmentioning
confidence: 89%
“…The number of UvrABC incision sites on a plasmid was calculated based on the Poisson distribution equation, P(0) = e −n , where n = number of UvrABC incisions. The data for Cr(III)-modified DNA were cited from our previous paper (8). Identification of Cr(III)-(gallate) 2 and Cr(III)-(EGA) 2 adduct formation sites in exon 5 (A), exon 7 (B), and exon 8 (C) in the p53 gene sequence by the UvrABC incision method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations